2018
DOI: 10.1589/jpts.30.1301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an underwear-type hip abduction orthosis on sitting balance and sit-to-stand activities in children with spastic cerebral palsy

Abstract: [Purpose] Hip dislocation and subluxation are common in patients with cerebral palsy (CP). Hip abduction orthoses are used to prevent and treat these problems. This study investigated the effects of an underwear-type hip abduction orthosis on sitting balance and sit-to-stand (STS) activity in children with spastic CP. [Participants and Methods] This trial had a cross-over design. Eight children aged 6 to 18 years old with spastic CP and Gross Motor Function Classification level III and IV were randomly allocate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Meanwhile, several studies regarding nonsurgical treatment for hip displacement, including various types of hip abduction braces, postural alignment seating systems, and botulinum toxin injection, have reported inconsistent results . In previous research, we showed that a seating system with medial knee support could act as a fulcrum, thereby accelerating progressive hip displacement in patients with nonambulatory spastic cerebral palsy .…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Meanwhile, several studies regarding nonsurgical treatment for hip displacement, including various types of hip abduction braces, postural alignment seating systems, and botulinum toxin injection, have reported inconsistent results . In previous research, we showed that a seating system with medial knee support could act as a fulcrum, thereby accelerating progressive hip displacement in patients with nonambulatory spastic cerebral palsy .…”
Section: Introductionmentioning
confidence: 83%
“…Meanwhile, several studies regarding nonsurgical treatment for hip displacement, including various types of hip abduction braces, postural alignment seating systems, and botulinum toxin injection, have reported inconsistent results. 15 , 16 , 17 , 18 , 19 , 20 In previous research, we showed that a seating system with medial knee support could act as a fulcrum, thereby accelerating progressive hip displacement in patients with nonambulatory spastic cerebral palsy. 21 In a follow-up study, the electromyographic activity of adductor muscles was significantly decreased after introducing a dynamic hip compression bandage, suggesting potential benefits.…”
Section: Introductionmentioning
confidence: 98%
“…Children with cerebral palsy (CP) have musculoskeletal impairments, which are often associated with comorbidities such as cognitive disorders, which directly interfere in acquiring essential motor skills to perform daily activities and participating in the environment in which they live (Ahmadi, O'Neil, Fragala‐Pinkham, Lennon, & Trost, 2018; Graham, Paget, & Wimalasundera, 2019). Spastic CP is the most common clinical form (85%) (Novak, 2011; Zanini, Cemin, & Peralles, 2009), which presents a higher risk of developing secondary complications (Jeffries, Fiss, McCoy, & Bartlett, 2016; Kusumoto et al, 2018) such as foot deformities due to the alteration in tonus, with equinus being among the most frequently observed (Kedem & Scher, 2015; Miller, 2018). Biomechanical foot misalignments are regularly addressed through a recommendation of orthoses, with the ankle‐foot orthosis (AFO) preferably being prescribed (Miller, 2018).…”
Section: Introductionmentioning
confidence: 99%